2017
DOI: 10.1111/ajo.12690
|View full text |Cite
|
Sign up to set email alerts
|

Very preterm birth before arrival at hospital

Abstract: Very preterm birth before arrival is more common in teenagers and is associated with significantly increased risks of perinatal and infant mortality compared with birth in a hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
3
10
0
1
Order By: Relevance
“…The increase in risk for fetus and newborns is well known [6,[31][32][33], Our results for hypothermia [2,3,33], polycythemia [2] and neonatal hospitalizations [33] are similar to those found in other studies. An increase in perinatal mortality was also reported by other studies [20,34], which seems consistent with the increase in risks of stillbirths and in-hospital neonatal deaths observed in the present study. However, the risk of maternal mortality has rarely been studied.…”
Section: Level Of Urbanizationsupporting
confidence: 93%
“…The increase in risk for fetus and newborns is well known [6,[31][32][33], Our results for hypothermia [2,3,33], polycythemia [2] and neonatal hospitalizations [33] are similar to those found in other studies. An increase in perinatal mortality was also reported by other studies [20,34], which seems consistent with the increase in risks of stillbirths and in-hospital neonatal deaths observed in the present study. However, the risk of maternal mortality has rarely been studied.…”
Section: Level Of Urbanizationsupporting
confidence: 93%
“…In this large national register study, we found that in recent years The annual UOHD rate in our study population was higher than in earlier studies in Finland (1.0-2.5 per 1000 births 4 ) and Norway (6.8 per 1000 births 1 ). In Finland, the annual rate of UOHDs increased significantly over the study period, with a similar trend throughout UOHDs are more likely to involve mothers who are younger 4,10,18 or older, 1,4,19 are unmarried, TA B L E 2 Risk factor analysis for unplanned out-of-hospital deliveries or a lower socioeconomic status, 6,18,20,21 have a lack of or less access to prenatal care, 2,3,9,18,20,22 have more previous deliveries, [1][2][3][4]6,9,[18][19][20][21][22] have fewer previous cesarean deliveries, 22 have lower GA at delivery, 1,2,4,6,10,18 and experience shorter duration of labor. 2,12 Our findings are in line with previous studies.…”
Section: Discussionmentioning
confidence: 69%
“…UOHDs carry an increased risk of perinatal and neonatal mortality, [1][2][3][4][5][6][7][8][9] including infants born preterm and low birthweight. 1,5,[9][10][11] We assessed risk factors associated with UOHDs in our earlier work and showed that risk factors associated with UOHDs were smoking during pregnancy, short labor, higher number of previous deliveries, single status, a distance from home to the delivery unit of more than 35 km and fewer prenatal visits. 12 One previous study, revealing risk factors for adverse neonatal outcome, 13 found that multiparity, prematurity, maternal pathology and neonatal hypothermia were independent risk factors of neonatal mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…One Australian study reported that 11% of women attended by EMTs during labour gave birth before arriving at hospital; of these, 27% were recorded with antenatal and/or intrapartum complications, while 22% of the babies were recorded with an Apgar score lower than 7 (Flanagan, Lord, & Barnes, ). Risk factors associated with both maternal and neonatal outcomes in unplanned out‐of‐hospital births include maternal characteristics (young maternal age, low socio‐economic status, immigrant background, smoking), pregnancy‐related factors (multiparity, placental conditions, low birthweight, prematurity, infections, concealed pregnancy) and poor antenatal care (Boland et al, ; Engjom, Morken, Høydahl, Norheim, & Klungsøyr, ; Gunnarsson, Fasting, Skogvoll, Smárason, & Salvesen, ; Jones et al, ; Nguyen et al, ; Unterscheider et al, ).…”
Section: Introductionmentioning
confidence: 99%